Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Gunung Semesta Elektrika - Sadeli, Melly Silviany; Syarif, Mahmud; Anggarini, Desy Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the influence of motivation and work discipline on employee performance at PT. Gunung Semesta Elektrika. The population in this research consists of 36 employees of the company. Data collection techniques involved observations and questionnaires distributed to all employees to obtain valid and reliable information from the field. The data were analyzed using multiple linear regression with the assistance of SPSS version 24.The results of this study indicate that the motivation variable does not have a significant effect on employee performance, as shown by the value of t = 1.003 < t table = 2.03452. In contrast, the work discipline variable has a positive and significant effect on employee performance, with a t value of 4.235 > t table = 2.03452. Simultaneously, motivation and work discipline have a positive and significant effect on employee performance, as shown by the F value of 77.180 > F table = 3.28. These findings suggest that the company should continue to maintain and improve employee motivation and work discipline to achieve faster and more efficient organizational progress in the future.